Validitas e-LKPD Bermuatan Profil Pelajar Pancasila pada Materi Protista - Putri, Rossanita Truelovin Hadi (LPPM Universitas KH.A.Wahab Hasbullah Jombang, 2024)
ABSTRACT The Pancasila student profile is a form of implementing the noble values of Pancasila in learning. Learning that contains character values and competencies characteristic of learning includes the Pancasila student profile. In line with developments in science and technology, today's learning media is integrated with renewable technology and the internet, for example, the learning media of electronic student activity sheets or E-LKPD. This research aims to describe the validity of the electronic worksheet containing the profile of Pancasila students on protist material. Electronic worksheet development refers to the 4D method, which consists of the define, design, develop, and disseminate stages. The research instrument is a validation sheet that material experts and education experts will validate. The results of the electronic worksheet development show validity with a percentage of agreement of 94% in the valid category. Based on the results of this assessment, it can be concluded that the electronic worksheet, which was developed with a Pancasila student profile on protist material, was declared valid and suitable for use by students. KEYWORDS: Electronic Worksheet, Pancasila Student Profile, Protist ABSTRAK Profil pelajar Pancasila merupakan suatu bentuk implementasi nilai-nilai luhur Pancasila pada suatu pembelajaran. Pembelajaran yang berisi nilai karakter serta kompetensi yang menjadi karakteristik pembelajaran bermuatan profil pelajar Pancasila. Selaras dengan perkembangan IPTEK, media pembelajaran masa kini sudah terintegrasi dengan teknologi terbaharukan dan internet, contohnya media pembelajaran lembar kegiatan peserta didik elektronik atau E-LKPD. Tujuan penelitian ini ialah mendeskripsikan validitas E-LKPD bermuatan profil pelajar Pancasila pada materi protista. Pengembangan E-LKPD mengacu pada metode 4D yang terdiri atas tahapan define, design, develop, dan disseminate. Instrumen penelitian berupa lembar validasi yang akan divalidasi oleh ahli materi dan ahli pendidikan. Hasil dari pengembangan E-LKPD menunjukkan validitas dengan percentage of agreement sebesar 94% dengan kategori valid. Berdasarkan hasil penilaian tersebut dapat disimpulkan bahwa E-LKPD yang dikembangkan dengan bermuatan profil pelajar Pancasila pada materi protista dinyatakan valid dan layak digunakan pada peserta didik. KATA KUNCI: e-LKPD, Profil Pelajar Pancasila, Protista